Global change on the Blue Planet - Annie Bourbonnais (Nature Portfolio, 2021)
Oceans and cryosphere are immediately affected by human-induced climate change. Our Editorial Board members present viewpoints on the most pressing and fruitful avenues of research on frozen and liquid water, and the transition from one to the other.